Resilience of Palestinian Children in the West Bank: A Systematic Review of School-Based Programs - Helsa Nasution; Luthfiah Mawar; M. Agung Rahmadi; Olivia Putri Natasya; Maya Dwi Harianti; Icha Putri Padilah; Nurzahara Sihombing; Naysila Prasetio; Nafiza Rizky Ramadhani Lubis (PPNI UNIMMAN, 2026)
This study systematically analyzes the effectiveness of school-based resilience programs designed for Palestinian children in the West Bank through a systematic review of 47 programs implemented over the period 2010–2023. The meta-analysis encompasses 12,847 participants aged 6–18 years from 89 schools and demonstrates a significant increase in resilience scores with a large effect size (d = 0.76, p < .001), accompanied by a substantial reduction in psychological trauma symptoms (r = -0.64, p < .001) and marked improvements in academic functioning (β = 0.58, p < .01). Programs integrating mindfulness approaches and psychosocial support exhibited the strongest effects (η² = 0.42), followed by expressive arts interventions (η² = 0.38) and play therapy (η² = 0.35), collectively underscoring the critical importance of non-conventional approaches in contexts of protracted conflict. Multilevel regression analysis revealed that a minimum program duration of 12 weeks and the level of family engagement contributed significantly to enhanced intervention effectiveness (R² = 0.67, p < .001). These findings extend the results of Qouta (2020) and Jabr et al. (2013) on child resilience in conflict zones, while offering an original contribution through the identification of specific program components most responsive to the Palestinian context. In particular, the integration of local cultural elements and the strengthening of collective identity were shown to increase program effectiveness by up to 43% compared with universal approaches, a pattern that has not been systematically documented in the previous literature.